Transmission of Eastern Equine Encephalitis Virus From an Organ Donor to 3 Transplant Recipients. (29th October 2018) - Pouch, Stephanie M; Katugaha, Shalika B; Shieh, Wun-Ju; Annambhotla, Pallavi; Walker, William L; Basavaraju, Sridhar V; Jones, Jefferson; Huynh, Thanhthao; Reagan-Steiner, Sarah; Bhatnagar, Julu; Grimm, Kacie; Stramer, Susan L; et al.
Abstract: Background: In fall 2017, 3 solid organ transplant (SOT) recipients from a common donor developed encephalitis within 1 week of transplantation, prompting suspicion of transplant-transmitted infection. Eastern equine encephalitis virus (EEEV) infection was identified during testing of endomyocardial tissue from the heart recipient. Methods: We reviewed medical records of the organ donor and transplant recipients and tested serum, whole blood, cerebrospinal fluid, and tissue from the donor and recipients for evidence of EEEV infection by multiple assays. We investigated blood transfusion as a possible source of organ donor infection by testing remaining components and serum specimens from blood donors. We reviewed data from the pretransplant organ donor evaluation and local EEEV surveillance. Results: We found laboratory evidence of recent EEEV infection in all organ recipients and the common donor. Serum collected from the organ donor upon hospital admission tested negative, but subsequent samples obtained prior to organ recovery were positive for EEEV RNA. There was no evidence of EEEV infection among donors of the 8 blood products transfused into the organ donor or in products derived from these donations. Veterinary and mosquito surveillance showed recent EEEV activity in counties nearby the organ donor's county of residence. Neuroinvasive EEEV infection directly contributed to the death of 1 organ recipient and likely contributed to death in another. Conclusions: Our investigation demonstrated EEEV transmission through SOT. Mosquito-borne transmission of EEEV to the organ donor was the likely source of infection. Clinicians should be aware of EEEV as a cause of transplant-associated encephalitis. Abstract : We describe the first reported transmission of eastern equine encephalitis virus (EEEV) infection through solid organ transplant. The organ donor was likely infected with EEEV via mosquito-borne transmission. Clinicians should be aware of EEEV as a cause of transplant-associated encephalitis.